(untitled) (Forum Theologicum Sardicense, 2025)
The goal of this article is to present the major theological points of Judges 3:12-30 (the deliverance cycle about Ehud and his mission as a judge), and, to arrive at a generalization about Israel‘s religious fervor in the setting of the Book of Judges. The commentary on the narratological aspects of the material in Judges 3:12-30 underscores a literary feature, i.e. a history of sequential deliverers, who bear the name ‚judges‘, fight the war of YHWH and have an immense practical effect on the Israelite community.